The Design of Books - Wilson Adrian (Reinhold Publishing Corporation, 1967)
Introduction, The Art of the Layout, Typography, Printing Methods, Paper, The Anatomy of the Book, Design Approaches, Binding, Jackets and Paperback Covers, Trade Book Design, Textbooks and References and Manuals, Limited Editions, Index.
Introduction, The Art of the Layout, Typography, Printing Methods, Paper, The Anatomy of the Book, Design Approaches, Binding, Jackets and Paperback Covers, Trade Book Design, Textbooks and References and Manuals, Limited Editions, Index.